Guia para wetlands urbanas de águas pluviais no Brasil - Ventura, Thaís Calixtro da Rocha (2023)
Constructed wetlands are multifunctional infrastructures that can be used to solve urban stormwater problems. These infrastructures are defined as artificial systems designed to mimic natural wetlands, using the same physical, chemical and biological processes to treat water. Usually conceived as small-scale solutions, they are most effective applied at the basin scale, distributed systematically and connected to the existing hydrological network, becoming part of the system's hierarchy. However, there is a shortage of material in Portuguese, especially contains a text that is accessible to decision-makers who do not have the technical framework and to Brazilian engineers and architects, taking into account our urbanization scenario, the existing infrastructures in the country, how constructed wetlands can be applied in the Brazilian context and their implications in the urban environment. Given these reasons, the Guidelines to Urban Stormwater Wetlands in Brazil is presented as an illustrative and conceptual work that presents the concept of constructed wetlands and their benefits, recommends typologies and explains how they work and how they should be applied in the urban context. These typologies can be adapted to different locations, scales, climates and functions, introducing heterogeneity into the urban landscape, influencing local biodiversity and ecosystem services, stimulating the creation of rich public spaces, pleasing to the public and with urban resilience.